EFFECTS OF CONTROLLED PHYSICAL TRAINING IN PATIENTS WITH HEART FAILURE - Stoičkov, Filip; Stoičkov, Ivan; Stoičkov, Viktor (Srpski medicinski časopis Lekarske komore, 2025)
Heart failure (HF) is a clinical syndrome characterized by cardiac symptoms (e.g., breathlessness, ankle swelling, and fatigue), which may be accompanied by signs (e.g., elevated jugular venous pressure, pulmonary crackles, and peripheral edema). Patients with HF often experience frequent hospitalizations, impaired quality of life, and shortened life expectancy. They also have decreased exercise capacity, primarily due to impaired hemodynamics within the active skeletal muscles. Patients with HF should undergo a cardiopulmonary exercise test to assess their activity level and type, as well as to perform risk stratification. The initial step should include evaluating the patient’s current exercise capacity and needs, then creating a personalized exercise program that details the types of exercises, their intensity, repetitions, duration in minutes per session, and the number of days per week allocated for training. Cycling (either on a stationary or regular bicycle) and walking are recommended because they are aerobic, dynamic forms of exercise. Aerobic training should be performed 3–5 times a week (30–60 minutes per session), with emphasis on interval training. This type of training enhances skeletal muscle strength and endurance, leading to increased muscle mass. In patients with heart failure and cachexia, resistance training is advised, combining both isotonic and isometric exercises. This type of training should be performed twice a week for 12 to 20 minutes per session. Resistance training also enhances skeletal muscle strength and endurance and encourages muscle growth. Physical training enhances skeletal muscle mass, fiber diameter, strength, endurance, and exercise capacity.
Keywords: heart failure; aerobic training; physical exercises; physical work capacity